In vitro evaluation of a new endodontic device for assessment of canal cleanliness - Randolph Cross; Gianluca Gambarini
A new testing device (Endocator, Endocator Inc, Aptos, CA, USA) has been recently developed to assess presence of remaining organic debris inside canals, In the present study the reliability of the device was assessed in vitro by checking the risk of possible cross-contamination during the sampling procedure. Five new syringes were used for sampling procedure in five artificial canals which had been previously filled with organic and inorganic debris (contaminated canals). The recorded Endocator measurement were noted as Group 0. Other five new syringes were used for sampling procedures in artificial canals in which no instrumentation, debridement or filling with debris had been performed (untouched canals). The recorded Endocator measurement were noted as Group A (sterile syringes). In Group B (non-sterile syringes) the sampling procedure in the untouched canals was repeated by using the same 5 syringes previously used for sampling in the contaminated canals. In all cases procedure precisely followed the instruction of use (IFU) provided by the manufacturer. . Descriptive analysis was performed to determine mean and standard deviation (SD) of the findings for the 3 groups. Paired T-test with Bonferroni correction was executed to find out significant differences (p<0.05) between the 3 groups. Results showed that, even if the canals were same and all well cleaned, Group B provided significantly higher mean values than Group A (p<0.05). In Group O canals (non-cleaned, contaminated canals) mean values were significantly higher than the other two groups (p<0.05) . Results showed a potential risk that even a minimal cross-contamination can significantly affect Endocator measurements due to the high sensitivity of the system. Therefore, authors suggested to use a new sterile syringe for each sampling procedure and proposed manufacturer should write this recommendation in the IFU (Instruction of Use) of the product.